2011
DOI: 10.1111/j.1365-2966.2011.18834.x
|View full text |Cite
|
Sign up to set email alerts
|

An XMM-Newton view of the ‘bare’ nucleus of Fairall 9★

Abstract: We present the spectral results from a 130-ks observation, obtained from the X-ray Multi-Mirror Mission-Newton (XMM-Newton) observatory, of the type I Seyfert galaxy Fairall 9. An X-ray hardness ratio analysis of the light curves reveals a 'softer-when-brighter' behaviour which is typical of radio-quiet type I Seyfert galaxies. Moreover, we analyse the high spectral resolution data of the reflection grating spectrometer and we do not find any significant evidence supporting the presence of warm absorber in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
42
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 69 publications
(104 reference statements)
8
42
2
Order By: Relevance
“…The reason why Suzaku spectra for Fairall 9 have received the attention of several studies is that the good energy resolution of the CCD detectors for measuring the crucial Fe Kα line profile, combined with the simultaneous sensitive coverage above 10 keV, provides a significant advance over previous capabilities for constraining the X-ray reflection spectrum and fluorescent line emission. Early observations of Fairall 9 with ASCA (Reynolds 1997) and XMM-Newton (Gondoin et al 2001;Emmanoulopoulos et al 2011) lacked the high-energy coverage. Nevertheless, a broad Fe Kα line (the principal feature required for constraining black-hole spin) was reported for the ASCA observation (Reynolds 1997) and for a 2009 XMM-Newton observation (Emmanoulopoulos et al 2011), but for an earlier XMM-Newton observation in 2000, Gondoin et al (2001) reported no detection of a broad Fe Kα line.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The reason why Suzaku spectra for Fairall 9 have received the attention of several studies is that the good energy resolution of the CCD detectors for measuring the crucial Fe Kα line profile, combined with the simultaneous sensitive coverage above 10 keV, provides a significant advance over previous capabilities for constraining the X-ray reflection spectrum and fluorescent line emission. Early observations of Fairall 9 with ASCA (Reynolds 1997) and XMM-Newton (Gondoin et al 2001;Emmanoulopoulos et al 2011) lacked the high-energy coverage. Nevertheless, a broad Fe Kα line (the principal feature required for constraining black-hole spin) was reported for the ASCA observation (Reynolds 1997) and for a 2009 XMM-Newton observation (Emmanoulopoulos et al 2011), but for an earlier XMM-Newton observation in 2000, Gondoin et al (2001) reported no detection of a broad Fe Kα line.…”
Section: Introductionmentioning
confidence: 99%
“…Early observations of Fairall 9 with ASCA (Reynolds 1997) and XMM-Newton (Gondoin et al 2001;Emmanoulopoulos et al 2011) lacked the high-energy coverage. Nevertheless, a broad Fe Kα line (the principal feature required for constraining black-hole spin) was reported for the ASCA observation (Reynolds 1997) and for a 2009 XMM-Newton observation (Emmanoulopoulos et al 2011), but for an earlier XMM-Newton observation in 2000, Gondoin et al (2001) reported no detection of a broad Fe Kα line. More recently, Fairall 9 was targeted by a Swift monitoring campaign and three new XMM-Newton observations, one of them simultaneous with NuSTAR (Lohfink et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ark 120 (or Arakelian 120) is a nearby (z = 0.032713, Osterbrock & Phillips 1977;Theureau et al 2005) and X-ray-bright ( =´- ; Patrick et al 2011;Baumgartner et al 2013) bare nucleus Seyfert 1. Along with its sister AGN, Fairall 9 (Emmanoulopoulos et al 2011;Lohfink et al 2012), it is the prototype example of a bare AGN. Indeed, it is one of the brightest and cleanest bare AGNs known, displaying neither intrinsic reddening in its IR/optical continuum nor evidence for absorption in UV and X-rays (Reynolds 1997;Crenshaw et al 1999), allowing a clear view of the innermost regions of the AGN.…”
Section: Introductionmentioning
confidence: 99%